FAILURE MECHANISM OF FATIGUE FRACTURE AND LIFE ANALYSIS FOR BOLTED JOINT OF AIRCRAFT STRUCTURE - FAN JunLing; ZHANG Wei; JIAO Ting; ZHAO YanGuang (Jixie qiangdu)
With respect to the fatigue failure of typical bolted joints of aircraft subjected to the random block spectrum, the micro-observation technology was used to analyze the macro and micro fracture morphology characteristics, and to reveal the fatigue failure mode and micro failure mechanism of bolted joint. Combined with the fatigue load spectrum and micro fatigue strip characteristics of the bolted joint, the fatigue crack propagation and initiation life were quantitatively derived based on the Paris formula, and the relation between fatigue crack length to the load cycle number and flight hour are respectively developed. The results show that the fatigue crack of the bolted joint originates from the bottom surface of the bolted joints with stress concentration, showing the multi-source mode. The fracture surface possesses typical fatigue characteristics, including crack source zone, crack growth zone and instantaneous fracture zone. It is also found that the two-stage function formula can properly characterize the evolution law between the fatigue crack growth length to the cycle number and flight time during the whole fatigue life. The fatigue crack growth and initiation life were calculated as 3 147.7 and 615.4 hours, and the configuration and manufacturing process of the bolted joint need to be improved to meet the requirements of safety life design.